Gastrointestinal mucosal damages caused by ingestion of corrosive substances: A case study of hydrochloric acid and sodium hydroxide - Yusuf, Fauzi; Abubakar, Azzaki; Maghfirah, Desi; Heltomi, Mirza; Isitua, Chinwe C. (Narra Sains Indonesia, 2023)
Ingestion of corrosive substances is most common in children, while in adults causes more severe damages. Massive ingestion of corrosive substances results in severe damage to the gastrointestinal tract and oropharynx if not treated properly. Corrosive substances with pH<2 or >12 can result in severe esophageal damage with either colliquative (alkaline) or coagulative (acidic) necrosis and, at the same time various gastrointestinal injuries could lead to late post-corrosive complications. The aim of the case study was to report the gastrointestinal mucosal damages due to hydrochloric acid (HCl) and sodium hydroxide (NaOH) ingestion. A 55-year-old male patient was presented to the emergency room with a chief complaint of vomiting an hour before admission. Continuous vomiting with a volume of approximately 10–20 cc per vomit. The vomit was initially bluish and turned in to blackish brown over time. Other complaints included nausea, rapid breathing, heartburn, and burning mouth and throat, and had weakness and dizziness. The patient accidentally drank floor cleaning liquid containing HCl. The patient was diagnosed with hematemesis due to ulceration of esophageal, gastric, and duodenal mucosa induced by HCl. Tracheoesophageal fistula developed later in the patient as a long-term complication. Another a 22-year-old male patient was presented to the emergency room with chief complaints of nausea and vomiting an hour before admission. Headache and slight tightness were also experienced. The patient mouth felt burned pain in the solar plexus and frothy saliva. An hour earlier, the patient attempted suicide by drinking two bottles of floor cleaning liquid due to economic problems. The patient was diagnosed with erosive mucosal esophagogastroduodenum induced by NaOH. These cases highlight that intoxication with corrosive substances can complicate damage to the gastrointestinal mucosal and damage features depend on the type of substance concentration and quantity of the corrosive substance.